2022
DOI: 10.3389/fcell.2022.841523
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Cardiovascular Diseases: Potential Targets for Treatment

Abstract: Cardiovascular diseases (CVDs) are serious public health issues and are responsible for nearly one-third of global deaths. Mitochondrial dysfunction is accountable for the development of most CVDs. Mitochondria produce adenosine triphosphate through oxidative phosphorylation and inevitably generate reactive oxygen species (ROS). Excessive ROS causes mitochondrial dysfunction and cell death. Mitochondria can protect against these damages via the regulation of mitochondrial homeostasis. In recent years, mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 236 publications
0
48
0
Order By: Relevance
“…Available studies have demonstrated that mitochondrial biogenesis is impaired in patients with diabetes mellitus in terms of redox homeostasis, fission/fusion, and respiratory chain activity. ( Rovira-Llopis et al, Apr 2017 ) Also, it has been demonstrated that patients with essential hypertension and cardiovascular disorders have some extent of mitochondrial dysfunction ( Ding et al, Oct 2013 , Yang et al, 2022 ). Therefore, patients’ comorbidities, as risk factors of CiLI, are justifiable through mitochondrial dysfunction.…”
Section: Risk Factors Of Covid-induced Liver Injury and How Mitochond...mentioning
confidence: 99%
“…Available studies have demonstrated that mitochondrial biogenesis is impaired in patients with diabetes mellitus in terms of redox homeostasis, fission/fusion, and respiratory chain activity. ( Rovira-Llopis et al, Apr 2017 ) Also, it has been demonstrated that patients with essential hypertension and cardiovascular disorders have some extent of mitochondrial dysfunction ( Ding et al, Oct 2013 , Yang et al, 2022 ). Therefore, patients’ comorbidities, as risk factors of CiLI, are justifiable through mitochondrial dysfunction.…”
Section: Risk Factors Of Covid-induced Liver Injury and How Mitochond...mentioning
confidence: 99%
“…The oxidation-dependent activation of specific molecular pathways leading to cell damage has been pointed out, from seminal observation on the role of mitochondria alteration in diabetic complications [ 168 ] to more recent analysis of the role played by oxidative stress in micro- and macro-angiopathy [ 169 ]. Thus, the role of mitochondria-derived ROS is fundamental in CVD [ 170 ], and mitochondria homeostasis has been proposed as a therapeutic target also in the context of aging and age-associated diseases, as recently reviewed [ 171 ]. Nonetheless, the dysregulation of NOX isoform activity, which plays a fundamental control of vascular functions (oxygen sensing and vascular tone regulation), is involved in CVD [ 172 ], in atherosclerosis [ 173 ], and in the development of kidney disease associated with hypertension and diabetes [ 174 ].…”
Section: Oxidative (Di)stress and Diseasementioning
confidence: 99%
“…Mitochondria provide ATP mainly from the oxidation of fatty acids, approximately 40–60%, and the rest from the oxidation of ketone bodies, amino acids, and pyruvate (derived from glucose and lactate) ( 105 , 106 ). Therefore, the remodeling of myocardial energy metabolism consists mainly of disorders of cardiac metabolic substrates and intracellular mitochondrial dysfunction ( 4 , 107 , 108 ).…”
Section: Nicotinamide Adenine Dinucleotide Phosphate Oxidase Affects ...mentioning
confidence: 99%